TOLERANCE WITHOUT LIBERALISM - M Khusna Amal; Norshahrir Saat (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2021)
There has been a rising Islamic fundamentalism, and intolerance cases in contemporary Indonesia. The fundamentalism problem in Indonesia particularly points to the Wahhābi for its puritanical ideology as the root of the intolerance cases. This article aims to analyse Indonesia’s largest Muslim organization, Nahdlatul Ulama (NU) and its responses towards the Wahhābi group. Being the forefront for the struggle against fundamentalist Muslim groups in post-New Order Indonesia, this article argues that NU adopts an intolerant approach in dealing with Wahhābi groups and their Islamic dakwah (preaching) activism. Taking a close look at a local branch of NU in Jember, East Java, the organisation’s approach is indeed ambiguous. On the one hand, NU calls for religious moderation, pluralism, and anti-violence approaches, but on the other hand, it also violates the principle of pluralism and democracy and is prone to authoritarianism for banning the Wahabi group’s rights to establish their educational institution in Jember. Based on a series of field research, this article contributes to the complexities of NU’s responses towards religious pluralism and the limits of the NU’s tolerance in contemporary Indonesia.